Root analysis social-structural violence from the thinking of Tomas Hobbes - Calcín Figueroa, Eduardo (2020)
Hobbes (1588-1679) conducted an analysis of society from a materialistic understanding of man. His state of nature led him to postulate a confrontation of man with other men who have their same aspirations for power and dominance. In this way, the State as a result of a pact between men would have the duty to guarantee the survival of all men by applying the laws, enforcing the duties and respecting the rights. Your thinking should be read within the context in which it arises because it allows you to understand history and the search for the rationality of social facts.